(untitled) (Applied Biological Research, 2015)
To elucidate the distribution of lipids, acid and alkaline phosphatase in different parts of adrenal gland at various stages of gestation in goat the present study was conducted on 24 healthy and normal foetii of non descript goat (Capra hircus) varying from day old to 150 days of gestation at CVS&AH, Mathura (India) The foetii were assigned into three groups according to their gestational ages: group I (0-50 days), group II (51-100 days) and group III (101 days - till term). Capsule showed traces to negative reaction in group-II but was devoid of lipids in group-III. Cytoplasm of foetal cortical cells and definitive cortex showed slight reaction for lipids but showed moderate reaction as the age advanced. The cytoplasm of medullary cells was devoid of lipids. Capsule showed moderate, whereas foetal cortex showed weak acid and alkaline phosphatase reactions.